Education and learning: preliminary findings from the Young Lives Round 5 Survey in Ethiopia - Pankhurst, A; Araya, M; Woldehanna, T (Young Lives, 2017)
This fact sheet presents findings from the fifth round of the Young Lives survey in 2016. Young Lives has followed two cohorts of children, born seven years apart. This fact sheet gives a snapshot of key education indicators for 15-year-olds in 2016 (Younger Cohort) and compares that to the data for 15-year-olds in 2009 (Older Cohort) to show changes in children’s education over that 7-year period. Despite a significant increase in school enrolment for both boys and girls, grade progression often remains slow, especially for children from rural sites and poorer households. Moreover, there are large disparities in learning levels between children from different socio-economic groups, as measured by maths and vocabulary tests.